PENGARUH PERTUMBUHAN MODAL, DAN PERTUMBUHAN ASET TERHADAP RISK BASED CAPITAL, PREMI NETTO DAN PROFITABILITAS PADA PERUSAHAAN ASURANSI JIWA - Ardi Ferdiyanto admin (Universitas Slamet Riyadi, 2014)
Insurance business has different properties and characteristics of the type of service business in general. Insurance business took over the risks of other parties so that the insurance company to solid risk if not properly managed. Basic insurance business is a public trust, especially in terms of financial capacity company to meet claims obligations and other liabilities on time. Effect of capital growth, and the growth of the Risk Based Capital assets, net premiums and profitability in life insurance companies in Indonesia. This research is a case study, a life insurance company in Indonesia as the population in this study. The samples in this study using purposive sampling method, in order to obtain a sample of 30 life insurance companies in Indonesia. Risk Based Capital, Net Premiums, profitability, asset growth, capital growth. The results of research conducted analysis shows that there are two variables are variables that asset growth has positive influence on Risk Based Capital while variable capital growth negatively affect the Risk Based Capital. The results of the second test showed that the two variables are variable capital growth and asset growth has positive influence on the growth of net premium. While the third test results indicate that the asset growth variables negatively affect the profitability of the life insurance company. Keywords: Risk Based Capital, Net Premiums, asset growth, capital growth.